(untitled) (Texas Journal of Philology, Culture and History, 2022)
The article discusses the peculiarities of Phraseological units which are proved by prominent linguists. The author highlights diversity in the usage of those stable units such as their history and culture. Reasonable suggestions are presented to prove how to clarify the meaning of phraseological units and their classification according to the structure in a particular speech as well as in what sphere they can be used.